Supervision of Beneficial Owners in Limited Liability Companies (Comparative Study of Indonesia-Germany Law) - Herry Soebagyo; Kurnia Mulia Ki; Ade Saptomo; Hotma Banjarnahor; Ramlan (International Journal of Scientific Multidisciplinary Research, 2023)
The purpose of this study is to find out and analyze the general beneficial owner regulation in Germany, specifically related to fines, information transparency, and the role of Notaries in the registration of beneficial owner information and to know and analyze what Indonesia can implement lessons to improve beneficial owner regulations beforehand. The type of research in this study is normative juridical. Based on the research that has been done, the results obtained are. As for the learned that Indonesia can learn from Germany, namely the application of fines for parties who do not register beneficial owner information, then provide a separate container to hold beneficial owner information data, and provide access for other parties to register the beneficial owner where so far, it can only be done by a Notary